A geography of real estate securitization and its multiple space-temporal dimensions. - Ferreira, Joao Vitor de Souza [UNESP] (2024)
The aim of this article is a spatial and temporal analysis of residential real estate securitization processes in Brazil. In this way, it highlights two points that are still considered to be neglected by the literature: on one side, the empirical dimension for understanding these processes, in particular the necessary methodological procedures, and on the other side the geographical, necessarily spatial and temporal nature of their understanding. It is understood that the reading of real estate securitization should not be limited to an issue term or the analysis of just one year but should understand that the securitization process extends and accumulates in time-space. To this end, the paper uses two main references: on the one hand, national and international theoretical analyses and, on the other, national information about the Certificados de Recebiveis Imobiliarios (CRIs) from 2011 to 2020.